2021
DOI: 10.1053/j.gastro.2021.06.023
|View full text |Cite
|
Sign up to set email alerts
|

Esophageal Hypervigilance and Symptom-Specific Anxiety in Patients with Eosinophilic Esophagitis

Abstract: BACKGROUND & AIMS: Patient symptom reporting often does not correlate with the pathophysiological markers of esophageal disease, including eosinophilic esophagitis (EoE). Esophageal hypervigilance and symptom-specific anxiety are emerging as important considerations in understanding symptom reporting. As such, we aimed to conduct the first study of these constructs in EoE. METHODS: A retrospective review of an EoE patient registry was conducted and included eosinophils per high power field (from esophagogastro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
62
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(67 citation statements)
references
References 42 publications
2
62
0
3
Order By: Relevance
“…Taken together, particularly (young) males that are diagnosed with EoE may be more at risk of impaired HRQOL, specifically related to food impaction. In addition to this, a recent study by Taft et al 45 observed that many EoE patients have elevated hypervigilance (ie, heightened focus on physical symptoms) and symptom specific anxiety such as swallowing anxiety, both being associated with worst reported EoE symptoms and poor HRQOL. These observations in mental health research emphasizes the importance of understanding the psychosocial issues being faced by EoE patients in clinical practice.…”
Section: Discussionmentioning
confidence: 95%
“…Taken together, particularly (young) males that are diagnosed with EoE may be more at risk of impaired HRQOL, specifically related to food impaction. In addition to this, a recent study by Taft et al 45 observed that many EoE patients have elevated hypervigilance (ie, heightened focus on physical symptoms) and symptom specific anxiety such as swallowing anxiety, both being associated with worst reported EoE symptoms and poor HRQOL. These observations in mental health research emphasizes the importance of understanding the psychosocial issues being faced by EoE patients in clinical practice.…”
Section: Discussionmentioning
confidence: 95%
“…Fundamental limitations to the reliance on symptoms and histology for disease management are mitigated by incorporating a measure of endoscopic activity. 58,59 In children, symptoms can be nonspecific and include poor intake as well as avoidant restrictive food intake disorders, which may lead to an underappreciation of dysphagia. In adults, reports of dysphagia severity can also be affected by patient anxiety and hypervigilance and diminished by modifications to eating behaviors.…”
Section: Endoscopic Gradingmentioning
confidence: 99%
“…Furthermore, it is well known that improvement in symptoms does not necessarily correlate with endoscopic or histologic measures of disease activity, especially in patients with fibrostenotic disease [14,15]. Finally, oesophageal hypervigilance and symptom-specific anxiety may contribute to patient-reported symptoms [16 ▪ ].…”
Section: How Do We Define Refractory Eosinophilic Esophagitis?mentioning
confidence: 99%